FAKTOR-FAKTOR YANG MEMENGARUHI KETIDAKLENGKAPAN IMUNISASI DASAR PADA BAYI - Amaliah, Lili; Kamaruddin, Mustamir; Sunaeni, Sunaeni; Cahyani, Desy Dwi (Ensiklopedia of Journal, 2025)
Abstract: Based on data obtained from the Lelogama Health Center, it is known that there are several types of complete basic immunizations that are less than the set target. The purpose of the study was to determine the factors that influence the incompleteness of basic immunization in infants. The research design used in this study was cross sectional. The research was conducted at Lelogama Health Center. The research was conducted in July 2024. The population is all mothers who have babies aged 9-24 months which amounted to 235 people. The sample amounted to 70 people. The sampling technique used in this study was purposive sampling. Data analysis was done univariate and bivariate. The results showed a relationship between maternal education (p value: 0.021) and service distance (p value: 0.002). It is recommended that mothers of toddlers are advised to understand the importance of immunization for the health of babies now and in the future, especially with regard to diseases that should be minimized by immunization.Keywords: Distance to service, immunization, maternal education.